Model Konseptual Intervensi Kesehatan Mental Berbasis AI-Cognitive Behavioral Therapy (AI-CBT) pada Generasi Z - Annisa Fadillah (Jurnal Bimbingan dan Konseling Ar-Rahman, 2026)
This study aimed to develop a conceptual model of Artificial Intelligence–Cognitive Behavioral Therapy (AI-CBT) for Generation Z using a grounded theory approach. The study was motivated by the increasing prevalence of mental health issues, particularly anxiety and emotional regulation difficulties, associated with intensive digital technology use among Generation Z. A qualitative grounded theory design was employed to explore participants’ experiences and generate conceptual categories from the data. Participants included high school students, school counselors, and professional counselors selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis and analyzed using open, axial, and selective coding procedures. The findings revealed a core category: the need for adaptive, personalized, and technology-accessible mental health services. This category was connected to Generation Z characteristics, factors contributing to mental health problems, counseling service needs, CBT intervention components, and the role of Artificial Intelligence in counseling. These relationships formed the basis of the proposed AI-CBT model, which consists of three components: input (individual characteristics and psychological concerns), process (AI-supported CBT techniques, including chatbot interactions, automated cognitive restructuring, emotional monitoring, sentiment analysis, personalized feedback, and adaptive support), and output (improved emotional regulation and reduced anxiety). The study provides a foundation for developing and empirically testing technology-driven counseling interventions. _____________________________________________________________Penelitian ini bertujuan mengembangkan model konseptual Artificial Intelligence–Cognitive Behavioral Therapy (AI-CBT) bagi Generasi Z dengan menggunakan pendekatan grounded theory. Penelitian ini dilatarbelakangi oleh meningkatnya permasalahan kesehatan mental, khususnya kecemasan dan kesulitan regulasi emosi, yang berkaitan dengan intensitas penggunaan teknologi digital pada Generasi Z. Desain penelitian kualitatif grounded theory digunakan untuk mengeksplorasi pengalaman partisipan dan menghasilkan kategori-kategori konseptual yang muncul dari data. Partisipan penelitian terdiri atas siswa sekolah menengah, guru bimbingan dan konseling, serta konselor profesional yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara mendalam, observasi, dan analisis dokumen, kemudian dianalisis menggunakan prosedur open coding, axial coding, dan selective coding. Hasil penelitian mengidentifikasi kategori inti berupa kebutuhan akan layanan kesehatan mental yang adaptif, personal, dan mudah diakses melalui teknologi. Kategori ini terhubung dengan karakteristik Generasi Z, faktor-faktor penyebab masalah kesehatan mental, kebutuhan layanan konseling, komponen intervensi CBT, serta peran kecerdasan buatan dalam proses konseling. Hubungan antarkategori tersebut membentuk model AI-CBT yang terdiri atas tiga komponen utama, yaitu input (karakteristik individu dan permasalahan psikologis), proses (penerapan teknik CBT berbantuan AI melalui chatbot, restrukturisasi kognitif otomatis, pemantauan emosi, analisis sentimen, umpan balik personal, dan dukungan adaptif), serta output (peningkatan regulasi emosi dan penurunan tingkat kecemasan). Temuan ini memberikan landasan bagi pengembangan dan pengujian empiris intervensi konseling berbasis teknologi.